Lack of Genetic Differentiation between Two Geographically Diverse Samples of Candida albicans Isolated from Patients Infected with Human Immunodeficiency Virus - Xu, Jianping (American Society for Microbiology, 1999)
The patterns of genetic variation of samples of Candida albicans isolated from patients infected with human immunodeficiency virus in Durham, N.C., and Vitória, Brazil, were compared. Genotypes for 126 strains were obtained at 16 polymorphic restriction sites distributed on nine PCR fragments. The results indicated evidence of clonality both within and between these two geographically diverse samples. The samples are genetically very similar, with little evidence of genetic differentiation.